The “Prostaja Mova” as a Bearer of Polish Influence on the Russian Chancery (prikaznyj) Language in Late Sixteenth and Early Seventeenth Century - Павловна Гарбуль, Людмила (Slavistica Vilnensis, 2009)
The article is devoted to the issue of the Polish influence on the Russian chancery (prikaznyj) language, which was of particular importance for the formation process of a new type of literary Russian. Using diplomatic correspondence from the era of Muscovite Russia as the source of study, the author provides generalized data on the intensity and profundity of the Polish influence on the lexical-semantic system of Russian as expressed through active mediation of the “prostaja mova”. However, the mova’s function was much broader. As a result, the author emphasizes its importance in the creation of the prerequisites necessary for change in the language of seventeenth-century Muscovite Russia.